Seated-Baduanjin as an adjuvant rehabilitation treatment for dysfunctional ventilatory weaning response: A case report. Issue 34 (August 2018) - Chen, Minggui; Zeng, Rui-Xiang; Liang, Xuefei; Hu, Xiyan; Kong, Lili; Wang, Jingjing; Guo, Liheng; Zhang, Min-Zhou; Zhang, Xiaoxuan
Abstract: Rationale: Seated-Baduanjin as adjuvant rehabilitation treatment in a patient with Dysfunctional ventilatory weaning response(DVWR) is extremely rare, and we report a case of a patient's rehabilitation exercise who suffered from DVWR. Patient concerns: A 62-year-old patient was admitted for dyspnea for more than a month after surgery. Diagnoses: On arrival, the patient was conscious but anxious, and he had difficulty breathing. When attempting to disconnect the ventilator, the patient's autonomous respiration > 25 times /min, and the heart rate > 120 times /min. He had to rely on the ventilator to survive. According to the characteristics of the patient, we considered the patient with DVWR. Interventions: We provided the same essential treatment as the last hospital and performed the Seated-Baduanjin for the patient which was a new form of bed exercise, 2 times a day, 30 minutes each time. Outcomes: The patient showed a gradual improvement in breathing and muscle strength. Lessons: In this case report, the Seated-Baduanjin showed a remarkable therapeutic effect on a patient and might be an adjuvant treatment for DVWR.